O acento secundário no português arcaico - Costa, Daniel Soares da [UNESP] (2012)
This paper aimsto study secondary stressinArchaic Portuguese demonstrating its limits of occurrence and its behavior through the Metrical Theory by Hayes (1995). The data was collected by means of a new methodology in the study of the prosody of ancient periods of the language. This methodology is based on the observation of matching and mismatching of musical and linguistic prominences of poetic texts with musical notation.